The effects of strategic intervention material with Edpuzzle-hosted Video Lesson (EdSIM) as a remediation tool for Grade 9 students in solving problems involving triangle similarity and right triangles - Del Puerto, Kim Gabrielle Marin (Animo Repository, 2023)
Strategic Intervention Materials and video lessons in the classroom are two well-explored ideas in the education sector concerning improving students’ mathematical performance. However, there have been no recorded attempts in the existing literature to integrate teacher-made video lessons in implementing strategic intervention materials to support learning the unmastered skills in mathematics. Thus, this study was undertaken to develop, utilize, and evaluate the effect of Edpuzzle video lesson-based Strategic Intervention Material (EdSIM) as a remediation tool for Grade 9 learners with unmastered mathematics competency in solving problems involving triangle similarity and right triangles. This study employed a classroom-based action research design and explanatory sequential mixed method approach where quantitative data was collected first, followed by qualitative data to explain the quantitative findings more in-depth. Deming's (1993) Plan-Do-Study-Act model was the researcher's roadmap for achieving this study's objectives. The EdSIM has been deemed suitable and appropriate as a remediation material based on the evaluators' high ratings. The student’s performance in the SIM activities was found to be very low, while their achievement level on the assessment card was characterized as moving toward mastery. In the Edpuzzle quizzes, learners performed at an average level. The results of the tests revealed a significant increase in the student’s level of mastery before and after the remediation. Learners improved from a mastery level of low to average. Therefore, the EdSIM can be considered an effective remedial tool in enhancing learners’ mastery of the least learned competency. The participants perceived the EdSIM as a helpful, enjoyable, and student-friendly tool for learning the least learned competency. They regarded the video lesson as the most salient feature of EdSIM and emphasized that learning the concept was made easier with the help of the video. The findings of this study serve as a guide in developing appropriate intervention materials, such as EdSIM, that can effectively address underperformance and cater to the diverse needs of students across different learning modalities. Keywords: strategic intervention material, teacher-made video lessons, Edpuzzle